Data for "Epidemiology of invasive pneumococcal disease in Southwest Sweden during the first eleven years after the introduction of general childhood pneumococcal vaccination" - Härnqvist, Tor; Bergman, Karin; Backhaus, Erik; Dahl, Mats; Kolberg, Helena; Ström Turesson, Caroline; Olander, Malin; Nilsson, Staffan; Andersson, Rune; Skovbjerg, Susann; Karlsson, Johanna (University of Gothenburg, 2026)
This dataset contains pseudonymised data on sex, age, clinical manifestations, and comorbidities for 2,280 individuals with invasive pneumococcal disease (IPD) in Region Västra Götaland during the post-introduction period following the inclusion of pneumococcal vaccination in the childhood immunisation programme in 2009 through 2019. Data were retrieved from patient medical records based on information provided by the microbiological laboratories serving all hospitals in the Västra Götaland Region regarding IPD episodes.

Detta dataset innehåller pseudonymiserade data för kön, ålder, kliniska manifestationer och komorbiditet för 2280 individer med invasiv pneumokocksjukdom (eng invasive pneumococcal disease, förkortat IPD) i Västra Götalandsregionen under perioden efter införandet av pneumokockvaccination i barnvaccinationsprogrammet 2009 till och med 2019. Data är inhämtad från patientjournaler baserat på uppgifter från de mikrobiologiska laboratorierna som servar samtliga sjukhus i Västra Götalandsregionen om IPD-episoder.
Data för "Epidemiology of invasive pneumococcal disease in Southwest Sweden during the first eleven years after the introduction of general childhood pneumococcal vaccination"
Keywords: Epidemiology; Epidemiologi; Meningitis, Pneumococcal; Pneumokockmeningit; Pneumonia, Pneumococcal; Pneumokockpneumoni; Comorbidity; Komorbiditet; Bacteremia; Bakteriemi; VACCINATION; VACCINATION; PCV10; PCV10; PCV7; PCV7; PPV23; PPV23; PCV13; PCV13; Invasive pneumococcal disease; Invasiv pneumokocksjukdom; Infectious Medicine; Infektionsmedicin